ANALISIS DIMENSI TEKS MODEL NORMAN FAIRCLOUGH PADA UJARAN KARAKTER THORFINN THORSSON DALAM ANIME VINLAND SAGA - Silvio Eggel Pratama; Dyah Wijayawati; M. Riyanton (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the limited number of linguistic studies that specifically examine the textual dimension of Critical Discourse Analysis in anime as a form of popular media. Vinland Saga presents dialogues that function not only as a means of communication, but also as a medium for constructing meaning, values, and the worldview of its characters. The research problem focuses on how the textual dimension of Norman Fairclough’s model is represented in the utterances of the character Thorfinn Thorsson. The aim of this study is to describe and analyze the linguistic features of the textual dimension, including lexical choice, grammatical structure, semantic relations, cohesion, and coherence in Thorfinn Thorsson’s utterances. This research employs a descriptive qualitative approach within the framework of Norman Fairclough’s Critical Discourse Analysis. The data consist of Thorfinn Thorsson’s utterances taken from selected episodes of Vinland Saga, collected through documentation techniques and analyzed systematically based on the categories of the textual dimension. The findings reveal that Thorfinn Thorsson’s utterances display consistent and distinctive linguistic patterns. Lexical choices tend to be direct and oriented toward physical action, grammatical structures frequently represent affirmation and self-denial, semantic relations are predominantly characterized by cause-and-effect patterns linking personal experience to acts of revenge, and cohesion and coherence are strongly constructed through causal conjunctions and referential devices that maintain textual unity. These findings demonstrate that the textual dimension plays a crucial role in representing the construction of meaning and the development of Thorfinn’s character in Vinland Saga.